DISAIN KURIKULUM INTER-DISIPLINER BERBASIS KKNI: PROGRAM STUDI ILMU KOMPUTER DENGAN FOKUS SOFT COMPUTING DAN INTELLIGENT SYSTEM - Armansyah, Armansyah; Kurniawan, Rakhmat (Jurnal Dedikasi Pendidikan, 2024)
The development of technology demands Computer Science graduates to have interdisciplinary knowledge and skills. Traditional curricula are less adaptive in addressing the dynamic industry needs and focus on developing soft skills. This article discusses the design of an interdisciplinary curriculum based on KKNI for Computer Science programs with a focus on soft computing and intelligent systems. This curriculum design integrates knowledge and skills from various disciplines, with an emphasis on the development of soft skills. The curriculum structure is divided into two tracks: the Mandatory Track focusing on the fundamental foundations of Computer Science and soft skills, and the Elective Track focusing on deepening interests and talents in the field of soft computing and intelligent systems, such as Artificial Neural Networks, Microcontrollers, Data Mining, Embedded Systems, Fuzzy Logic, and Computer Vision. This research adopts a Research and Development (R&D) approach with the ADDIE model. Data are collected through surveys, interviews, and document analysis. It is expected that this curriculum design will produce Computer Science graduates with comprehensive, adaptive knowledge and skills, ready for the digital era workforce, particularly in the field of soft computing and intelligent systems.